The Russia-Ukraine Conflict - Shaheen, Taghreed (2023)
Turkey's geographical location and historical ties with both Russia and Ukraine have shaped its unique position as a potential mediator in the Russia-Ukraine war. As a NATO member and an aspiring regional power, Turkey recognizes the risks posed by a protracted conflict on its doorstep and has actively sought to leverage its diplomatic channels to de-escalate tensions. Turkish leaders have engaged in intense shuttle diplomacy, facilitating direct talks between Russian and Ukrainian officials, and hosting high-level meetings in Turkey. Turkey's involvement in the Russia-Ukraine conflict has drawn international attention and gathered both praise and criticism. While some view Turkey's mediation efforts as a pragmatic and constructive approach to prevent further bloodshed, others express concerns about its ability to navigate the complexities of the conflict impartially. In light of these debates, the thesis analyzes Turkey’s active engagement in mediating and maintaining a proactive approach in the Russia-Ukraine conflict, which underscores its growing regional influence and highlights the need for inclusive and multilateral approaches to resolve complex geopolitical crises.